Determination of five sulfonylurea herbicides in environmental waters and soil by ultra high performance liquid chromatography with tandem mass spectrometry after extraction using graphene. Issue 24 (12th November 2014) - Li, Cheng; Lu, Anxiang; Wang, Jihua; Li, Jie; Ping, Hua; Luan, Yunxia; Chen, Jiayi; Ha, Xuejiao
<x xml:space="preserve">Abstract</x> A fast and novel analytical method was developed for the determination of trace levels of sulfonylurea herbicides in water and soil samples. Graphene was used as a sorbent for extraction, and ultra high performance liquid chromatography with tandem mass spectrometry was used for quantification. Five sulfonylurea herbicides were preconcentrated from water samples using a graphene‐loaded packed cartridge, while extraction from soil samples was performed in a single step using graphene‐supported matrix solid‐phase dispersion. Under the optimized conditions, the calibration plots were linear in the range between 5 and 1000 ng/L for water samples, and between 1 and 200 ng/g for soil samples. All correlation coefficients (R) were >0.99. The limits of detection for water and soil samples were 0.28–0.53 ng/L and 0.08–0.26 ng/g, respectively. This method was successfully applied to the analysis of spiked samples of environmental water and soil, with recoveries ranging from 84.2–109.3 and 86.12–103.2%, respectively, all with relative standard deviations of <10%.